Tableau 2019.1 for data scientists - Bogicevic, Manja (Packt Publishing, 2019)
"What makes this training module different? This step-by-step guide is designed to give you practical and essential skills that anyone doing data visualization and analytics needs to have. You'll be able to boost your visualizations by learning techniques such as adding filters and quick filters, and using color schemas in dashboards. By the end of this course, you'll have the skills to make your Tableau data visualization projects a success by creating fascinating stories and offering invaluable guidance when strategic business decisions are being made."--Resource description page